PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PEN-DIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS IV SDN 13 PASAR REMAJA KOTA SAWAHLUNTO - Devigra Restu Ananda; Atri Waldi; Yesi Anita; Gita Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of fourth-grade students in Pancasila Education, where the learning process was still teacher-centered, dominated by conventional methods, lacked innovative learning models, and provided limited technology-integrated learning media. These conditions led to low active engagement, weak critical reasoning ability, low collaborative involvement in groups, and low student confidence. Baseline data showed that only about 46% of students had reached the Learning Objective Achievement Criteria (KKTP). This condition indicated the need to improve the learning process so that student learning outcomes could increase comprehensively. This study aimed to describe the lesson planning, the implementation of learning, and the improvement of Pancasila Education learning outcomes through the application of the Problem Based Learning (PBL) model in grade IV of SDN 13 Pasar Remaja, Sawahlunto City. This study used a Classroom Action Research (CAR) design with a mixed qualitative-quantitative approach. The research subjects were 24 fourth-grade students. The study was carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, tests, and documentation, and were analyzed descriptively, both quantitatively and qualitatively. The results showed that the application of the PBL model improved student learning outcomes in Pancasila Education. The quality of lesson planning (teaching modules) increased from 87.5% in Cycle I Meeting 1 to 95.83% in Cycle II. Teacher and student activity during learning also improved significantly, both reaching 96.42% in Cycle II with a very good qualification. The average score for the knowledge aspect rose from 70.84 (Cycle I Meeting 1) to 85.00 in Cycle II, with a mastery level of 95.83%, while the average score for the skills aspect rose from 68.75% to 88.50% in Cycle II. It can therefore be concluded that the Problem Based Learning (PBL) model is effective in improving student learning outcomes in Pancasila Education in grade IV of SDN 13 Pasar Remaja, Sawahlunto City.